Overexpression of ABA Receptor PYL10 Gene Confers Drought and Cold Tolerance to Indica Rice - Verma, Rakesh Kumar; Santosh Kumar, Vinjamuri Venkata; Yadav, Shashank Kumar; Pushkar, Suchitra; Rao, Mandali Venkateswara; Chinnusamy, Viswanathan (Frontiers in Plant Science, 2019)
Abscisic acid (ABA) plays versatile functions in regulating plant development and tolerance to various biotic and abiotic stresses. Towards elucidating the functions of one of the ABA receptors (ABARs) in rice, OsPYL10 was cloned from drought tolerant rice cv. Nagina 22 and was overexpressed under stress inducible RD29A promoter in a mega rice variety MTU1010 by using Agrobacterium mediated genetic transformation. Four single copy transgenic lines selected based on Southern blot analysis were used for physiological and molecular analysis. PYL10 receptor appears to regulate its ligand ABA accumulation as PYL10 overexpressing transgenics accumulated 2-3.3 fold higher levels of ABA than that of WT in flag leaf at anthesis under non-stress conditions. The enhanced accumulation of ABA was associated with enhanced expression of genes for ABA biosynthesis viz., ZEP1, NCED1, NCED2, NCED3 and NCED4 in transgenics than in WT plants. At seedling stage, PYL10 transgenics showed significantly higher survival rate under cold stress as compared with WT plants. qRT-PCR analysis showed that expression levels of cold responsive genes viz., DREB1F, MYB3R2, TPP1, COR410, DEHYDRIN and LEA3 were significantly higher in PYL10 overexpressing transgenic lines as compared to WT plants under cold stress. PYL10 transgenic and WT plants grown in the same pot were subjected to -80 kPa drought stress and recovery treatments at vegetative and reproductive stages. At vegetative stage drought stress, three overexpressing lines showed significantly higher grain yield (40-58%) and at reproductive stage drought stress one of these overexpression lines showed two-fold higher grain yield than that WT plants. Excised leaf water loss analysis showed that PYL10 transgenic lost about 20% less water than WT plants. At reproductive stage, OsPYL10 transgenic maintained higher RWC, membrane stability index, chlorophyll content, and accumulated lower amount of MDA and H2O2 as compared with WT plants. qRT-PCR analysis showed that expression levels of RAB16, Dehydrin, LEA3 and ABA45 were higher in PYL10 transgenics as compared with WT plants under drought stress. Thus overall results showed that OsPYL10 overexpression has potential to improve both drought and cold stress tolerance of indica rice.